2019
DOI: 10.1093/eurheartj/ehz835
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in heart failure

Abstract: The overall lifetime risk of heart failure (HF) is similar between men and women, however, there are marked sex differences in the landscape of this condition that are both important and under-recognized. Men are predisposed to HF with reduced ejection fraction (HFrEF), whereas women predominate in HF with preserved ejection fraction (HFpEF). Sex differences are also notable in the penetrance of genetic cardiomyopathies, risk factors, e.g. breast cancer which may be associated with cancer treatment-induced car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
436
4
23

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 521 publications
(490 citation statements)
references
References 130 publications
27
436
4
23
Order By: Relevance
“…1,2 The most recent trends according to data from 4 million individuals indicate that the absolute number of incident HF cases was 9% higher in men than in women, but among older individuals (>80 years), the absolute number of HF cases was higher in women ( Figure 1). 3 Whereas macrovascular coronary artery disease and myocardial infarction are leading causes of HF in men, [4][5][6][7] coronary microvascular dysfunction, hypertension and immuno-inflammatory mechanisms are thought to play a greater role in the development of HF in women. 4,8,9 Response of the myocardium to ischaemic injury and cardiovascular stress also differ between men and women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The most recent trends according to data from 4 million individuals indicate that the absolute number of incident HF cases was 9% higher in men than in women, but among older individuals (>80 years), the absolute number of HF cases was higher in women ( Figure 1). 3 Whereas macrovascular coronary artery disease and myocardial infarction are leading causes of HF in men, [4][5][6][7] coronary microvascular dysfunction, hypertension and immuno-inflammatory mechanisms are thought to play a greater role in the development of HF in women. 4,8,9 Response of the myocardium to ischaemic injury and cardiovascular stress also differ between men and women.…”
Section: Introductionmentioning
confidence: 99%
“…3 Whereas macrovascular coronary artery disease and myocardial infarction are leading causes of HF in men, [4][5][6][7] coronary microvascular dysfunction, hypertension and immuno-inflammatory mechanisms are thought to play a greater role in the development of HF in women. 4,8,9 Response of the myocardium to ischaemic injury and cardiovascular stress also differ between men and women. For instance, after an ischaemic insult to the heart, a ∼10-fold higher apoptotic rate in the peri-infarct region has been observed in men compared with women.…”
Section: Introductionmentioning
confidence: 99%
“…Men and women experience quite different cardiovascular disease susceptibility profiles and outcome, a feature that is poorly understood. Further, the effects of biologic sex on health, disease susceptibility and mortality are vastly understudied (1, 2). Recent studies showed that genetics contribute to sex-specific differences in fat tissue and cardiovascular and metabolic diseases (3).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the comorbidity burden shows sex-related disparities, with women more likely to be older, with higher New York Heart Association (NYHA) class and natriuretic peptide levels, affected by hypertension and chronic kidney disease, whereas males more likely to suffer from diabetes and ischaemic heart disease. 2,3 Despite the lower quality of life and the more severe symptoms, which have been repeatedly reported in women vs. men with HF, women appear to 'benefit' from a prognostic advantage which is consistent across the ejection fraction spectrum. 3 Sex-related disparities in HF treatment need also to be acknowledged.…”
mentioning
confidence: 95%
“…[3][4][5][6] Sex-related differences in pharmacokinetics and pharmacodynamics might influence the net benefit of HF medications and the occurrence of side effects in women vs. men, explaining, at least partially, the under-treatment often observed in women. 2 Based on these considerations, the need for solid data supporting an appropriate use of HF evidence-based therapies in women has become a burning issue. A previous meta-analysis of RCTs showed angiotensin-converting enzyme inhibitors (ACEi) and beta-blockers being effective regardless of sex.…”
mentioning
confidence: 99%